Предмет: Алгебра,
автор: SunAng
Решите уравнение
(x-2)(x^2+2x+1)=4(x+1)
Ответы
Автор ответа:
2
(x-2)(x^2+2x+1)=4(x+1)
(x-2)(x+1)(x+1)-4(x+1) = 0
(x+1)*((x-2)(x+1) - 4) = 0
(x+1)*(x^2 - 2x + x - 2 - 4) = 0
(x + 1)(x^2 - x - 6) = 0 {D=1+24 = 25 x12=(1 +- 5)/2 = 3 -2}
(x + 1)(x + 2)(x - 3) = 0
x1 = -1
x2 = -2
x3 = 3
Автор ответа:
1
Відповідь:
Пояснення:
Приложения:
Похожие вопросы
Предмет: Алгебра,
автор: yapridumalshutku
Предмет: Математика,
автор: ema2008
Предмет: Математика,
автор: helpmeplser
Предмет: Литература,
автор: daniniil
надо писать, что при х=-1 левая и правая части равны х=-1 это корень
и уже дальше делим на х+1, он уже не равен 0